Nonlinear Magneto-Electro-Mechanical Response of Physical Cross-Linked Magneto-Electric Polymer Gel - Fan, Xiwen; Wang, Yu; Wang, Bochao; Shen, Longjiang; Li, Jun; Xu, Zhenbang; Wang, Sheng; Gong, Xinglong (Frontiers in Materials, 2021)
Here, a novel magnetorheological polymer gel with carbon nanotubes and carbonyl iron particles mixed into the physical cross-linked polymer gel matrix is reported in this work. The resulting composites show unusual nonlinear magneto-electro-mechanical responses. Because of the low matrix viscosity, effective conductive paths formed by the CNTs are mobile and high-performance sensing characteristics are observed. In particular, due to the transient and mutable physical cross-linked bonds in the polymer gel, the electromechanical behavior is in a rate-dependent manner. External stimulus at high rate can significantly enhance the electrical resistance response during mechanical deformation. Meanwhile, the rheological properties can be regulated by the external magnetic field with adding the magnetic particles. This dual enhancement mechanism can further contribute to implement the active control of electromechanical performance. These polymer composites can be adopted as electromechanical sensitive sensors to measure the impact and vibration under different frequencies. There will be a great potential for this magnetorheological polymer gel in the application of intelligent vibration controls.